Problems and Difficulties in Teaching Turkish Grammar to Ukrainian Students at University Level - Sorokin, Sergii V.; Timkova, Tetiana (Journal of History Culture and Art Research, 2019)
The subject of this research paper is the teaching of Turkish as a foreign language. The authors’ more than twenty-year experience in teaching Turkish to university students constitutes the empirical foundation of this investigation. The theoretical and methodological basis of this research is the source criticism method, the experimental method, the questionnaire method of data collection and the statistical method. The history of foreign languages teaching methods is analysed, and special attention is paid to the approaches of teaching grammar, discussed in methodological works. Implicit and explicit approaches to the teaching of grammar are especially examined in this paper. The subject of this research is oriented at teaching Turkish as a major and training future specialists in Turkish interpreting/ translation and future teachers/ lecturers in Turkish, therefore, the authors of this paper stress upon the necessity of teaching grammar on the basis of conscious perception principle as a separate subject of study in strict integrity with the communicational approach. The list of problems and difficulties in learning Turkish grammar by Ukrainian students at University level was established as a result of this research as well as the sources of these difficulties are deduced which mostly originate in genetical and typological differences between the Ukrainian language, native for Ukrainian students, and Turkish, which is the language of their future professional activities. The mentioned difficulties are grouped on two levels which are morphology and syntax according to the level of difficulty for Ukrainian students in terms of the conscious perception of grammatical facts and phenomena and their subsequent application in actual practice. The ways of overcoming the problems and difficulties in teaching and learning Turkish grammar are also offered in this paper. At the same time textbooks and grammar manuals published in Turkey, Ukraine and European countries are examined in terms of grammar teaching. The grammatical subjects to be investigated in detail for increasing the level of mastering Turkish by Ukrainian students at universities are listed.